Model of Anticipation Guidance Through Family Centered Care (FCC) to Increase Family Competence in Newborn Baby - Ade Wulandari; Ni Putu Sumartini; H Ahmad (poltekkes kemenkes mataram, 2020)
Anticipation guidance based on Family-Centered Care (FCC) is a mentoring model for sharing information about baby care in order to prepare pregnant women and families to have competence in caring for babies. This study aims to determine the effect of FCC-based anticipatory guidance on family practices in baby care. This study designed as a quasi-experimental study using a control group conducted in the City of Bima from June to November 2018. The sample size studied was determined by the accidental sampling method with a sample size of 25 respondents for each group. The chi-square test has analyzed data. Research shows that there is no significant difference between FCC-based anticipation guidance and Early Breastfeeding Initiation (p = 0.358), umbilical cord care (p = 0.703) and breastfeeding (p = 0.375), however, the frequency of respondents receiving FCC-based anticipation guidance carries out IMD practices and breastfeeding alone up to the age of two months are greater than anticipatory guidance groups that are not FCC based. The family-centered anticipation guidance model through home visits needs to be applied to bring the distance closed between the community and health workers.